1990
DOI: 10.1021/bi00499a020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the changes in the structure and hydration of the nucleosome core particle at moderate ionic strengths

Abstract: In order to better understand the conformational changes induced in the nucleosome core particle by changes in the ionic strength of the media in the range from 0.1 to 0.6 M NaCl, we have conducted a very detailed structural analysis, combining circular dichroism, DNase I digestion, and sedimentation equilibrium. The results of such analysis indicate that the secondary structure of both DNA and histones exhibits small (approximately 5%) but noticeable changes as the salt increases within this range. In the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…A further conformational change to a less oblate form observed in this study by microscopy of particles prepared in the presence of 400 mM NaCl is supported by findings of a transition between 150 and 400 mM NaCl by fluorescence studies (9,11). This change is consistent with the overall structural change of the nucleosome characterized by Dong et al (50) in the range of 100 -600 mM NaCl. Using detailed physicochemical analyses in that study, it was concluded that both DNA and histones exhibit changes as salt is increased in this range, consistent with a trend to a more relaxed secondary structure (50).…”
Section: Discussionsupporting
confidence: 91%
“…A further conformational change to a less oblate form observed in this study by microscopy of particles prepared in the presence of 400 mM NaCl is supported by findings of a transition between 150 and 400 mM NaCl by fluorescence studies (9,11). This change is consistent with the overall structural change of the nucleosome characterized by Dong et al (50) in the range of 100 -600 mM NaCl. Using detailed physicochemical analyses in that study, it was concluded that both DNA and histones exhibit changes as salt is increased in this range, consistent with a trend to a more relaxed secondary structure (50).…”
Section: Discussionsupporting
confidence: 91%
“…We (25,32,33,47,48) and others (35, 49 -51) have shown that nucleosomes in solution are not static entities but rather they are highly transient structures. A dynamic equilibrium exists between the constitutive histone octamer and the nucleosomal DNA (32), which besides the ionic strength is also dependent on many other physical parameters such as temperature and sample concentration.…”
Section: Resultsmentioning
confidence: 63%
“…Initial studies revealed surprisingly few changes in the properties of mononucleosomes following trypsinization (92,93). The extended structure that mononucleosomes form as salt increases was not significantly altered by removal of the tails; nor were there significant changes in circular dichroism (CD) spectra.…”
Section: The Histone Amino Terminal Tailsmentioning
confidence: 99%